Studies on variability and genetic divergence in elite lines of garlic (Allium sativum L.) - R P Gupta, R K Singh, B K Dubey, (Journal of Spices and Aromatic Crops, 2012)
The study was conducted during 2006–07 to 2007–08 at Karnal (Haryana), to identify suitable genotypes of garlic for cultivation. The results revealed that a wide range of variability was recorded for gross yield, marketable yield, weight of 50 cloves, number of cloves per bulb, plant height and clove size index. Genotypic and phenotypic coefficients of variations were high for weight of 50 cloves, number of cloves per bulbs, marketable yield and clove size index. Heritability in broad sense ranged from 43.9 to 95.0%. High value of heritability was recorded for plant height followed by cloves per bulb, leaves per plant, weight of 50 cloves, weight of 20 bulbs, marketable yield, bulb size index, and neck thickness. A high estimate of genetic advance was showed by cloves per bulb followed by weight of 50 cloves, marketable yield and weight of 20 bulbs. High values of heritability, GCV and genetic advance as percent of mean were observed for cloves per bulb, weight of 50 cloves, marketable yield, and weight of 20 bulbs. The analysis of variance revealed significant divergence among the thirty two garlic advance lines for different traits, indicating sufficient genetic diversity among the cultivars. The cluster-VII had highest value of plant height (109.11 cm), gross yield (239.19 q ha-1) and minimum stemphylium intensity (2.08%). Cluster VI was promising for leaves per plant (9.51), bulb size index (15.88 cm2), weight of 20 bulbs (0.696 g) and marketable yield (159.05 q/ha). Cluster X was observed to be promising for bulb diameter (4.63 cm), clove diameter (1.33 cm), clove size index (3.58 cm2) and weight of 50 cloves (85.0 g). Therefore, it is suggested that selection of genotypes based upon the large cluster distances from all the clusters may lead to broad spectrum favorable genetic variability for bulb yield improvement.